Initiatives on a sustainable development strategy for Finnish biotechnology - Raine Hermans; Martti Kulvik (The Research Institute of the Finnish Economy (ETLA), 2005)
The need for the strategic initiatives for biotechnology strategy emerged in interviews with 90 Finnish biotechnology leaders in the ETLA Biotechnology Survey, conducted at the end of 2004. This paper discusses on the policy implications for the project on “The biotechnology industry as a part of the Finnish National Innovation System” financed by Tekes, the National Technology Agency of Finland. Tekes has strongly encouraged the formation of policy implications and strategic initiatives for the biotechnology sector of Finland. Healthcare technology has been regarded as the main application area of biotechnology, but the applications of plant and process biotechnology are gaining in importance. Irrespective of the application area, the technological interests and the market potential are global. A typical example is in the production of food, where products such as Golden rice and Bt (bacillus thuringiensis) wheat are discussed as a step towards balancing the global inequality of food production. However, this discussion paper focuses on the potential synergy between innovation clusters in a domestic context. We have identified global megatrends that impose a threat on the future well-being of Finland. Our aim has been to try to take advantage of the megatrends and turn them into opportunities within the context of sustainable development1: Firstly, the ageing population will induce a threat to the supply of public healthcare for everyone. Healthcare related “red” biotechnology might play an important role in the restriction of increases in healthcare costs by providing new cost-efficient healthcare applications. Additionally, some applications for functional food might offer pro-actively some positive health outcomes before there are any costs affected by an illness. In many cases, it would be more cost-efficient to create preventive mechanisms than treat those illnesses. Secondly, the extensive use of fossil fuels has been proclaimed as posing a major threat to the global bio-system. Thirdly, as oil reservoirs outside the Middle East are becoming depleted, the rising prices together with geographically skewed production will probably strain the existing economic balance. However, applications of plant “green” biotechnology and industrial “white” biotechnology could provide some solutions for producing, for example, bio-fuels instead of polluting fossil-fuels, as well as growing specified crops that take advantage of the Arctic dimension of the Finnish environment. Based on literature and the megatrends affecting Finland as a whole, we have outlined four innovation clusters:
Keywords: 330; Biotechnologie; Biotechnische Forschung; Forschungs- und Technologiepolitik; Internationaler Wettbewerb; Finnland